Impactos de políticas de desoneraç\~ao do setor produtivo: Uma avaliaç\~ao a partir de um modelo de geraç\~oes superpostas - Napole\~ao Luiz Costa da Silva; Marco Antônio Freitas Hollanda Cavalcanti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– In this paper we investigate the macroeconomic and welfare effects of recent proposals to reduce the tax burden on the production sector in Brazil. We evaluate two specific policy measures: a) the replacement of social security taxes with a consumption tax; and b) the provision of tax incentives to investment activities, as established in the Federal Government`s Program for Productive Development launched in May 2008. Our analysis is based on an overlapping generations model with uncertain lifetime and capital adjustment costs. According to our results, the replacement of social security taxes with a consumption tax has important macroeconomic and redistributive effects, generating significant welfare gains to the younger generations and losses to the older generations. With regard to the tax incentives provided by the Federal Government Program, we find a relatively small macroeconomic impact, which is probably due to the small reduction in effective taxation contained in the program.
Keywords: E60; H20; 330